Interventions to reduce sugar‐sweetened beverage consumption using a nudge approach in Victorian community sports settings. (11th November 2021) - Forsyth, Adrienne; Nicholson, Matthew; Skiadopoulos, Anne; Trakman, Gina; Devlin, Brooke; Belski, Regina; Randle, Erica; O'Halloran, Paul; Cameron, Matthew; Staley, Kiera
Abstract: Objective : To assess the effectiveness of interventions using a nudge approach to reduce sugar‐sweetened beverage purchases in community sports settings. Methods : A total of 155 community sporting organisations participating in VicHealth funded programs were invited to nominate a nudge based on a traffic light approach to drinks classification. These included limit red drinks, red drinks off display, water the cheapest option, and meal deals. Sales data was collected for a predetermined period prior to and following the introduction of the nudge. Nudges were classified initially on whether they were implemented to VicHealth standards. Appropriately implemented nudges were classified as successful if they achieved a relative decrease in sales from drinks classified as red. Results : In all, 148 organisations trialled 195 nudges; 15 (7.7%) were successful and 20 (10.3%) were appropriately implemented but unsuccessful. Limit red drinks was the most frequently attempted nudge (30.8%). Red drinks off display had the greatest rate of success (20.0%). Conclusions : Red drinks off display was the simplest and most successful nudge. Implications for public health : Guidelines limiting the display of sugar‐sweetened beverages may be an effective means of altering consumer behaviour.